CONSTRUING THE INTERLINK BETWEEN MULTIPLE INTELLIGENCE AND EXPLICIT VOCABULARY KNOWLEDGE: THE CASE OF INDONESIAN MADRASAH STUDENTS - NUSWAH ARROFAL HASANAH (Language-Edu, 2020)
Each person’s have abilities or intelligences supporting factors in process of learning English Foreign Language. These are 9 types of intelligence formulated by Gardner. The research will be predict and know what this multiple intelligence components have relationship with to explicit vocabulary knowledge. This research problem: Is there any Correlation between Multiple Intelligence Components and Explicit Vocabulary knowledge? And if yes, which one of them is the better predictor for Explicit Vocabulary knowledge?. The researcher use descriptive quantitative method especially the multiple regression analysis. The population of the study is all eight grade students at MTs Salafiyah Merakurak Tuban that are 69 students.There are two instruments to take some data which is to adopt the form of several sources of Multiple Intelligence Survey (MIS) from Kenzie (1999) in Gardner theory and Vocabulary Quiz. The result of the study shows that R Square is 0.282, it is known that the value of R Square equals to 0.282, this implies that variables predictors has simultaneous contributed on dependent variable equals to 28,2 %. Practically, the researcher concludes that from the result on the study are Existential Intelligence and Interpersonal Intelligence more contributed and significant to Explicit Vocabulary Knowledge.Keywords: Correlation, Multiple Intelligence, Explicit Vocabulary Knowledge